2015
DOI: 10.1111/agec.12206
|View full text |Cite
|
Sign up to set email alerts
|

Measuring public agricultural research and extension and estimating their impacts on agricultural productivity: new insights from U.S. evidence

Abstract: This article provides new estimates of the marginal product of public agricultural research and extension on state agricultural productivity for the U.S., using updated data and definitions, and forecasts of future agricultural productivity growth by state. The underlying rationale for a number of important decisions that underlie the data used in cost‐return estimates for public agricultural research and extension are presented. The parameters of the state productivity model are estimated from a panel of cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 29 publications
7
50
1
2
Order By: Relevance
“…The average social rate of return ranged from 14.35% in Model 2 to 39.56% in Model 1. These IRR rates are lower than the ones in [15] and [16] 12 . Table 9 reports the rates of return by production region.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…The average social rate of return ranged from 14.35% in Model 2 to 39.56% in Model 1. These IRR rates are lower than the ones in [15] and [16] 12 . Table 9 reports the rates of return by production region.…”
Section: Resultscontrasting
confidence: 54%
“…This [16] uses the same USDA data set, an updated R & D stock variable, construct spill-ins using the geographical proximity approach (our Model 1), use a different proxy for Extension, do not include roads and use a two-step approach regressing the USDA productivity index on research and extension variables. [14] uses the same two-step procedure but the productivity index and the research and extension stocks are obtained using a different data set and different functional specifications.…”
Section: Discussionmentioning
confidence: 99%
“…Extension information has always been partly a public and partly a private good, and as the boundaries shift between the two types of goods, pressures build to reform agricultural extension, in part to save scarce public resources (Umali‐Deininger ; Marsh and Pannell ). Data on global public extension funding and personnel are limited, but a gradual decline has occurred in real funding in several countries including the United States (Wang ), although less so when measured on a per‐farmer basis (Jin and Huffman ).…”
Section: Extension Changesmentioning
confidence: 99%
“…TFP growth there has only averaged about 1% in recent years (Fuglie and Rada ), although it does appear to be rising in the last decade in some countries. Economic rates of returns to agricultural extension in Sub‐Saharan Africa have frequently been reported in the range of 30–100%, although methodological issues cast doubt on the validity of the estimates in some studies (Jin and Huffman ; Pardey et al ). A metastudy of economic rates of return to agricultural research and extension found a mean rate of return of 58% for extension across 289 studies (Alston et al ).…”
Section: Effects Of Extension Changesmentioning
confidence: 99%
“…The public sector is the primary provider of agricultural R&D in developing countries 3 as well as the major source of agricultural innovation (Fan and Pardey 1997;Pardey 2009;Alston et al 2010;Hu et al 2011). For agriculture, public agricultural R&D undertaken in one area produces agricultural technology innovations that may spill over to public agricultural research efforts in other areas and expands the technologies available to farms and agri-business (Jin and Huffman 2016). An example is that, agricultural innovation on paddy rice created by public research institute in Jiangsu province can be easily transferred into agri-business and farmers in neighboring Anhui and Zhejiang province.…”
Section: Introductionmentioning
confidence: 99%